The Role of Legitimate Politics in Achieving Social Security (an Applied Study on Family Reform Bureaus in Jordan) - Abdel Salam Atwa Ali Al- Fandi; Hamza Ahmed Mohammed Abu Seileek (Yayasan Adra Karima Hubbi, 2024)
Background. This study is organized with an introduction and three sections: The Nature of Legitimate Politics and Societal Security, consisting of two subsections, The Importance and Nature of Legitimate Politics, consisting of two subsections, An Applied Study of the Family Reform Bureau in Jordan, consisting of two subsections. Method. This research aims to explain the role of legitimate politics in achieving community security and apply it to the family reform bureau in Jordan. Results. Societal security is an essential need for the growth and sustainability of society, and legitimate politics is the means to achieve it. The family reform bureau performs several tasks, including: reviewing cases transferred from the courts, accepting cases directly brought to the bureau for guidance or resolution of existing disputes, seeking preventive knowledge and guidance. The family reform bureau plays a central and effective role in achieving public security and reducing the divorce rate in society. Conclusion. In addition, field research can also be used as a complement, namely interviews supported by primary data.